2017
DOI: 10.1093/ckj/sfx138
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of enteral nutrition with sodium polystyrene sulfonate: effective, but beware the high prevalence of electrolyte derangements in clinical practice

Abstract: BackgroundCurrent treatment options for chronic hyperkalemia in children with chronic kidney disease include dietary restrictions or enteral sodium polystyrene sulfonate (SPS); however, dietary restrictions may compromise adequate nutrition and enteral SPS may be limited by palatability, adverse effects and feeding tube obstruction. A potentially safer alternative is to pretreat enteral nutrition (EN) with SPS prior to consumption. The purpose of this study was to evaluate the efficacy and safety of pretreatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
1
16
0
6
Order By: Relevance
“…The preparation and method of pretreatment of enteral nutrition with SPS had a similar methodology compared with other studies, so does not explain the in vivo and in vitro differences. Independent of potassium, sodium and calcium, Palma et al [ 18 ] found no significant difference in bicarbonate or chloride levels, which is consistent with the previous in vivo study by Thompson et al [ 12 ]. However, as demonstrated in other studies (see Table 1 ) [ 11 , 15 , 16 ], due to the non-specific binding nature of SPS, there may be significant, yet inconsistent effects on other essential trace elements such as zinc, copper and manganese.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The preparation and method of pretreatment of enteral nutrition with SPS had a similar methodology compared with other studies, so does not explain the in vivo and in vitro differences. Independent of potassium, sodium and calcium, Palma et al [ 18 ] found no significant difference in bicarbonate or chloride levels, which is consistent with the previous in vivo study by Thompson et al [ 12 ]. However, as demonstrated in other studies (see Table 1 ) [ 11 , 15 , 16 ], due to the non-specific binding nature of SPS, there may be significant, yet inconsistent effects on other essential trace elements such as zinc, copper and manganese.…”
supporting
confidence: 82%
“…The rates of clinical hypokalaemia (31.6%) and hypernatraemia (26.3%) described by Palma et al [ 18 ] mimic the in vitro findings on the potassium and sodium content of feeds following pretreatment with SPS [ 10–17 ], although the degree of electrolyte disturbance is less marked. For example, clinical hypernatraemia developed following SPS pretreatment in only five cases (26.3%), despite the reported increase in in vitro studies of sodium feed content by 86–527% [ 10 , 11 , 13–17 ].…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Thus, if this product is used, the powdered version should be chosen. Although considered to be safer than oral or rectal administration, there are still risks with the decanting process, including common risks of serious biochemical derangement (67) as it is not possible to remove all of the SPS solution from the decanted formula.…”
Section: Unique Adjustments To Enteral Feedingsmentioning
confidence: 99%